1988
DOI: 10.1016/0306-4530(88)90054-6
|View full text |Cite
|
Sign up to set email alerts
|

Systemic hormonal and physiological abnormalities in anxiety disorders

Abstract: Among the studies of systemic hormonal and physiological abnormalities associated with anxiety disorders, the most consistent and extensive findings suggest (a) peripheral adrenergic hyperactivity (including increases in norepinephrine but not epinephrine) and functional dysregulation, (b) increased incidence of mitral valve prolapse in panic patients, and (c) normal suppressibility of the hypothalamic-pituitary-adrenal cortical endocrine system with dexamethasone in panic patients. Other less-certain findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(35 citation statements)
references
References 197 publications
2
32
0
1
Order By: Relevance
“…Low levels of melatonin have also been reported in premenstrual dysphoric disorder [10] and panic disorder [11]. Conflicting results of melatonin levels were reported in eating disorders [12][13][14] as well as in schizophrenia [15,16].…”
Section: Melatonin and Psychiatric Disordersmentioning
confidence: 83%
“…Low levels of melatonin have also been reported in premenstrual dysphoric disorder [10] and panic disorder [11]. Conflicting results of melatonin levels were reported in eating disorders [12][13][14] as well as in schizophrenia [15,16].…”
Section: Melatonin and Psychiatric Disordersmentioning
confidence: 83%
“…Recently, we have reported significant elevations of saliva cortisol levels during spontaneously occurring panic attacks (Bandelow et al 2000a). Other authors, however, found normal baseline plasma levels in panic patients (Brambilla et al 1992;Cameron et al 1987;Cameron and Nesse 1988;Liebowitz et al 1985;Villacres et al 1987;Woods et al 1988). One possible explanation for these discrepant findings could be related to the observation from the present study showing that temporary withdrawal from smoking leads to a reduction of baseline cortisol levels, thus masking an overactive HPA axis in PD patients.…”
Section: The Hypothalamic-pituitary-adrenal System In Pdmentioning
confidence: 95%
“…Cameron ve arkadaşlarının panik bozukluğu ile ilgili yaptıkları bir çalışmada, panik bozukluğunda azalmış gece melatonin düzeyi saptanmış-tır. [124] Tüm bu veriler, melatonin hormonunun psikiyatri ile ilgili birçok hastalıkla ilişkili olduğunu ortaya koymaktadır. Günümüze kadar yapılan bu çalış-malar, melatoninin gelecekte de psikiyatri ile ilişkili hastalıkların incelenmesinde önemli bir yer tutacağını göstermektedir.…”
Section: Melatonin Ve Psikiyatrik Hastalıklarunclassified